2021
DOI: 10.1007/s12020-021-02883-y
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal development in 46,XY patients with NR5A1 mutations

Abstract: Purpose Mutations in the NR5A1 gene, encoding the transcription factor Steroidogenic Factor-1, are associated with a highly variable genital phenotype in patients with 46,XY differences of sex development (DSD). Our objective was to analyse the pubertal development in 46,XY patients with NR5A1 mutations by the evaluation of longitudinal clinical and hormonal data at pubertal age. Methods We retrospectively studied a cohort of 10 46,XY patients with a verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…The normal or subnormal testosterone levels with elevated LH levels suggested a compensated primary hypofunction of Leydig cells and explained the virilisation signs observed in the patient at puberty. This description is in line with that of Mönig et al., who studied 10 NR5A1 mutated patients during adolescence and puberty ( 24 ). Other authors also showed an impaired Sertoli cell function with a normal or subnormal Leydig cell function conserved at least until puberty ( 23 , 25 , 27 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The normal or subnormal testosterone levels with elevated LH levels suggested a compensated primary hypofunction of Leydig cells and explained the virilisation signs observed in the patient at puberty. This description is in line with that of Mönig et al., who studied 10 NR5A1 mutated patients during adolescence and puberty ( 24 ). Other authors also showed an impaired Sertoli cell function with a normal or subnormal Leydig cell function conserved at least until puberty ( 23 , 25 , 27 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, Mönig et al. reported an early pubertal development with an early increase in testosterone levels in three out of 10 cases ( 24 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[11] Ten NR5A1 variations were identified among German patients with 46,XY DSD with varying phenotypes in a cohort study. [12] In our case, a 12-year-old girl was diagnosed with 46,XY DSD due to NR5A1 mutation. The individual with 46,XY karyotype was noticed to have clitoromegaly, but otherwise normal female external genitalia, she has vellus hair on the upper lip, longer hair on the arms and legs, undescended dysplasia testes, no uterus, and ovaries.…”
Section: Discussion and Literature Reviewmentioning
confidence: 71%
“…[ 11 ] Ten NR5A1 variations were identified among German patients with 46,XY DSD with varying phenotypes in a cohort study. [ 12 ]…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%